The umbilical vein in the human fetus has a non‐linear growth pattern across gestation. Issue 3 (23rd June 2016) - Najafzadeh, Afrooz; Jacoby, Peter; Mattes, Eugen; Dickinson, Jan E
Abstract: Introduction and Objectives: Estimation of the umbilical venous blood flow volume relies on the diameter of the vein, which has been reported to be reduced in severely growth restricted fetuses. However, there is only limited information on the growth pattern of this vessel in the normal human fetus. The aim of this study is to examine the growth pattern of the umbilical vein across gestation in low‐risk human pregnancies. Methods: In a prospective, longitudinal ultrasound study of 136 low‐risk pregnancies, the internal diameter of the intra‐amniotic portion of the umbilical vein was measured at 18, 26 and 34 weeks of gestation. To investigate the growth pattern of the venous diameter, the ratios of diameters at 26 weeks to diameters at 18 weeks (ratio 1) and the ratios at 34 to 26 weeks (ratio 2) were also calculated. A paired‐sample t ‐test was performed to compare the means of the two ratios. Results: The mean diameter of the umbilical vein at 18 weeks was 2.8 mm (SD 0.40), 5.8 mm (SD 0.67) at 26 weeks and 7.6 mm (SD 0.98) at 34 weeks. The mean of ratio 1 was 2.06 (95% CI 2.01–2.14), which was significantly higher than ratio 2 (mean 1.33, 95% CI 1.29–1.36), P < 0.001. Conclusion: The umbilical venous diameter demonstrates a non‐linear growth pattern between 18 and 34 weeks of gestation. The diameter doubled in size between 18 and 26 weeks but grew at a slower rate between 26 and 34 weeks of gestation. This study provides new data on the normal growth pattern of the umbilical vein by identifying a period of gestation where its growth is accelerated.